Myricanol Inhibits Platelet Derived Growth Factor-BB-Induced Vascular Smooth Muscle Cells Proliferation and Migration in vitro and Intimal Hyperplasia in vivo by Targeting the Platelet-Derived Growth Factor Receptor-β and NF-κB Signaling - Fan, Siyuan; Wang, Cheng; Huang, Kai; Liang, Minglu (Frontiers in Physiology, 2022)
The abnormal proliferation and migration of Vascular smooth muscle cells (VSMCs) are related to many cardiovascular diseases, including atherosclerosis, restenosis after balloon angioplasty, hypertension, etc. Myricanol is a diarylheptanoid that can be separated from the bark of Myrica rubra. It has been reported that myricanol can anti-inflammatory, anti-cancer, anti-neurodegenerative, promote autophagic clearance of tau and prevent muscle atrophy. But its potential role in the cardiovascular field remains unknown. In this study, we investigated the effect of myricanol on the proliferation and migration of VSMCs in vitro and on the intimal hyperplasia in vivo. In vitro experiments, we found myricanol can inhibit the proliferation and migration of VSMCs induced by PDGF-BB. In terms of mechanism, the preincubation of myricanol can suppress the PDGF-BB induced phosphorylation of PDGFRβ and its downstream such as PLCγ1, Src, and MAPKs. In addition, NF-kB p65 translocation was also suppressed by myricanol. In vivo experiments, we found myricanol can suppress the intimal hyperplasia after wire ligation of the carotid artery in mice. These results may provide a new strategy for the prevention and treatment of coronary atherosclerosis and post-stent stenosis in the future.